“There is nothing that can prevent me from supporting her:” men’s perspectives on their involvement and support of women’s use of topical therapy for cervical precancer treatment in Kenya - Mungo, Chemtai; Adewumi, Konyin; Adoyo, Everlyn; Zulu, Graham; Goraya, Supreet Kaur; Ogollah, Cirillus; Omoto, Jackton; Ferrari, Renée M.; Rahangdale, Lisa (Frontiers in Oncology, 2024)
Purpose Cervical cancer disproportionately impacts women in low- and middle-income countries (LMICs). The World Health Organization’s (WHO) 90/70/90 strategy aims to eliminate cervical cancer by 2030 by increasing HPV vaccination coverage to 90%, screening 70% of eligible women, and effectively treating 90% of those with abnormal results by 2030, potentially preventing 62 million deaths in LMICs. LMICs, however, struggle with limited access to cervical precancer treatment, in part due to a lack of trained professionals and weak health systems. Effective non-surgical, self-administered, which have demonstrated efficacy in high-income countries, could bridge the treatment gap in LMICs and may be more scalable and cost-effective than provider-administered therapies. To inform feasibility studies in LMICs, data are needed on the role of male partners in influencing the acceptability and uptake of self-administered topical therapies, including their support of recommended abstinence and contraception guidelines associated with these therapies. Methods Between November 2022 and April 2023, we conducted five focus group discussions (FGDs) with men aged 25 to 65 years in Kenya to explore their perspective and perceived support regarding their female partners using topical self-administered therapies for cervical precancer treatment. The FGDs were moderated by local qualitative research assistants and conducted in local languages, transcribed, coded, and analyzed using qualitative description. Results Thirty-nine male participants meeting the eligibility criteria participated in five FGDs. The mean age of participants was 42.5 years. Most participants, 79.5%, had a female partner with a history of cervical precancer treatment, 5.1% did not, and 15.4% were unsure of their female partner’s prior precancer treatment history. The study aimed to assess men’s support of their female partners’ use of topical therapies for treating cervical precancer. We find that male participants strongly express acceptance and willingness to support their wives or partners in using such therapies, if available. Reported supportive behavior included permitting the use of the therapies and support of maintaining abstinence during the recommended times. Additionally, participants desired male involvement in clinic and community-based education about topical therapies to facilitate widespread support. Conclusion The use of self-administered topical therapies for cervical precancer treatment, if supported by efficacy studies in LMICs, may support achieving the WHO’s 2030 goal of 90% treatment access. We find that with adequate education, men express overwhelming support of their female partner’s use of topical therapies, including adherence to abstinence and contraception guidelines.